Regulatory links between the circadian clock and stress-induced biomolecular condensates - Gabriela Brown; Dawn H. Nagel (npj Biological Timing and Sleep)
Abstract The circadian clock is a conserved timekeeping mechanism that is essential for integrating different environmental cues such as light and temperature to coordinate biological processes with the time of day. While much is known about transcriptional regulation by the clock, the role of post-transcriptional regulation, particularly through sequestration into biomolecular condensate such as stress granules, remains less understood. Stress granules are dynamic RNA-protein assemblies that play a critical role in the cellular response to stress by sequestering mRNAs to regulate translation during stressful conditions. In animals and fungi, the circadian clock regulates stress granule formation and mRNA translation by controlling key factors such as eIF2α, which orchestrates the rhythmic sequestration and translation of specific mRNAs. In plants, it has been shown that some transcripts, despite coming from arrhythmic expression, are rhythmically translated. In addition, some clock-controlled genes (CCGs) are induced in response to heat stress only at the transcriptional level and not at the translational level. Together this highlights a layer of clock regulation beyond transcription. This review discusses the intersection between the circadian clock and heat stress-related biomolecular condensates across eukaryotes, with a particular focus on plants. We discuss how the clock may regulate stress granule dynamics and preferential translation of mRNAs at specific times of the day or during stress responses, thereby enhancing cellular function and energy efficiency. By integrating evidence from animals, fungi, and plants, we highlight emerging questions regarding the role of biomolecular condensates as post-transcriptional mechanisms in controlling circadian rhythms and stress tolerance in plants.